SARS‐CoV‐2 respiratory viral loads and association with clinical and biological features. Issue 3 (29th September 2020) - Biguenet, Adrien; Bouiller, Kevin; Marty‐Quinternet, Solène; Brunel, Anne‐Sophie; Chirouze, Catherine; Lepiller, Quentin
Abstract: To determine the distribution of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) respiratory viral loads (VL) during the acute phase of infection and their correlation with clinical presentation and inflammation‐related biomarkers. Nasopharyngeal swabs from 453 adult SARS‐CoV‐2‐infected patients from the Department of Infectious Diseases, Besançon, France, were collected at the time of admission or consultation for reverse transcriptase polymerase chain reaction (RT‐PCR) analysis. Clinical information and concentrations of biological parameters (C‐reactive protein [CRP], fibrinogen, lactate dehydrogenase [LDH], prealbumin) were noticed. Mean respiratory VL homogeneously decreased from 7.2 log10 copies/ml (95% confidence interval [CI]: 6.6–7.8) on the first day of symptoms until 4.6 log10 copies/ml (95% CI: 3.8–5.4) at day 10 (slope = −0.24; R 2 = .95). VL were poorly correlated with COVID‐19 symptoms and outcome, excepted for dyspnea and anosmia, which were significantly associated with lower VL ( p < .05). CRP, fibrinogen, and LDH concentrations significantly increased over the first 10 days (median CRP concentrations from 36.8 mg/L at days 0–1 to 99.5 mg/L at days 8–10; p < .01), whereas prealbumin concentrations tended to decrease. Since SARS‐CoV‐2 respiratory VL regularly decrease in the acute phase of infection, determining the level of VL may help predicting the onset of virus shedding in a specific patient. However, the role of SARS‐CoV‐2 VL as a biomarker of severity is limited.